PENGARUH TERAPI RELAKSASI BENSON TERHADAP TEKANAN DARAH PADA LANSIA HIPERTENSI - Utomo, Gisandy Rio; Khoiriyah, Siti; Mustajab, Abdullah Azam; Alviana, Fifi (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2025)
Background: Hypertension is caused by structural and functional changes in the peripheral blood vessels that lead to changes in blood pressure. A non-pharmacological treatment that can be used for hypertension is Benson relaxation therapy. Benson relaxation technique is a type of deep breathing exercise technique accompanied by spiritual language that the client believes in. Objective: To investigate the effect of Benson relaxation therapy on blood pressure in hypertensive elderly people in Bumireho village. Method: A pre- experimental research design combined with a pre-experimental design and a pre- post-test design on one group. The methodology used in this study was total sampling with a total sample of 43 respondents who are hypertensive elderly people. Results: The p value of systolic blood pressure was 0.036 before the test and 0.002 after the test, while the diastolic blood pressure on the day before the test was 0.000 and 0.001 after the test. The obtained p value < 0.05 Conclusion: There is an effect of Benson therapy on blood pressure in hypertensive elderly people in Bumirejo village.